A literature review on the causal relationship between Occlusal Factors (OF) and Temporomandibular Disorders (TMD) III: experimental studies with artificial Occlusal Interferences (OI) - Acosta-Ortíz, Rodolfo; Roura-Lugo, Nelson (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: this is the third article in this series that aims to present a literature review about the causal relationship between occlusal factors (OF) and temporomandibular disorders (TMD). Methods: this article presents and analyzes experimental studies in which occlusal interferences (OI) were used according to parameters recommended by Mohl. Results and conclusions: the analysis reported in this article did not support any OF as causal in TMD development. Although some OI were associated to the development of TMD signs and symptoms, this was, in the best of the cases, transitory. Additionally, methodological aspects such as the short follow-up time, and lack of control groups in most of the studies made the information found questionable.